69 Hot Saline Irrigation for Haemostasis in Functional Endoscopic Sinus Surgery: A Systematic Review and Meta-Analysis. (28th February 2022) - Ranford, D.; Fu, B.; Surda, P.; Rudd, J.
Abstract: Aim: The aim of this study was to perform a systematic review and meta-analysis of existing evidence on the role of hot saline irrigation (HSI) in patients undergoing functional endoscopic sinus surgery (FESS) and its impact on the visibility of the surgical field (VSF). Method: A search of PubMed, Cochrane, Ovid (including Embase, Medline and Allied and Complementary Medicine Database) databases as well as Google Scholar was performed. Results: Three randomised control trials (RCT) were included. All three were pooled into meta-analysis which demonstrated a statistically significant better VSF (MD -0.51; 95% CI -0.84, -0.18; P = 0.003), a reduction in total blood loss (TBL) (MD -56.40ml; 95% CI -57.30. -55.51; P = <0.0001) and a reduction in operating time (OT) (MD -7.01mins; 95% CI 9.02mins; 95% CI -11.76, -6.28; P = <0.0001) during FESS in the HSI group compared with the room temperature irrigation control group. Further subgroup analysis of studies that did not use topical vasoconstrictors showed a significant reduction in TBL and OT. There were no reported adverse events related to HSI. Conclusions: This is the first systematic review that addresses HSI for haemostasis in FESS. The results suggest that HSI in FESS for chronic rhinosinusitis may significantly improve VSF, reduce TBL by 20% and decrease OT by 9 minutes. HSI is cheap and a readily available intervention with a low risk of morbidity and adverse events. However, there are limitations of the study due to significant heterogeneity of methods, quality, and size of the studies.